Analisis Bahasa Hukum dalam Hukum Pidana Islam - Hariyato, Hariyanto (JURNAL PENELITIAN KEISLAMAN, 2011)
The exact punishment for offenders of Islamic criminal law (jarîmah hudûd) has been clearly mentioned through the language of legal texts in the Qurâan and hadith. However, the realization of the sentence has been problematic and criticized by human rights proponents because they suggest that in contemporary life religious and legal discourses have to be in line with justice, truth, human rights and international law. This study aims to explore legal language of the Qurâan and hadith concerning Islamic criminal law. It shows that any reading and understanding on legal language should consider legal language and the meaning of legal language in various and respective contexts of human life. The truth of the legal language of Islamic criminal law is included in the truth of the religious knowledge, which is dogmatic.